Metabolic syndrome, hepatic fibrosis, and steatosis diagnosed by liver stiffness measurement and controlled attenuation parameter after liver transplantation: the impact on long-term survival. (3rd October 2022) - Eshraghian, Ahad; Fattahi, Mohammad Reza; Taghavi, Alireza; Shamsaeefar, Alireza; Mansoorian, Mohsenreza; Kazemi, Kourosh; Nikeghbalian, Saman; Malek-Hosseini, Seyed Ali
ABSTRACT: Background: Liver stiffness measurement (LSM) and controlled attenuation parameter (CAP) are used for diagnosis of liver fibrosis and steatosis. This study aimed to noninvasively evaluate hepatic steatosis and fibrosis in liver transplant recipients using CAP and LSM and the impact on survival of patients. Methods: In a prospective study, adult liver transplant recipients were included. CAP and LSM obtained during transient elastography (TE) were used for assessment of hepatic steatosis and fibrosis. Patients were followed during 4 years for mortality as the main outcome after liver transplantation. Results: From 296 patients, 24.7% and 25% of liver transplant recipients had liver steatosis and fibrosis in CAP and LSM, respectively. In multivariable Cox regression analysis, etiology of liver disease (NASH versus non-NASH) (HR: 3.125; 95% CI: 1.594–6.134; p = 0.001), and post-transplant diabetes mellitus (PTDM) (HR: 2.617; 95% CI: 1.396–4.926; p = 0.003) were associated with hepatic steatosis after liver transplantation. In multivariable Cox regression analysis, liver fibrosis was an independent predictor of mortality after liver transplantation (HR: 4.926; 95%CI: 1.779–13.513; p = 0.002). Conclusion: CAP and LS measurement during TE are useful methods for diagnosis of hepatic steatosis and fibrosis in liver transplant recipients. LS measurement might predict long-term survival of patients.